The Aesthetics and History of the Hub: The Effects of Changing Technology on Network Computer Music. - Gresham-Lancaster, Scot (Leonardo Music Journal, 1998)
Discusses the aesthetic and performance history of the music group Hub. Information on the interactive computer network music of the group; Impact of changes in technology on the music of the group; Details of experiments with software synthesis and the Internet.